Similar Morphologies but Different Origins: Hybrid Status of Two More Semi-creeping Taxa of Melastoma - Zou, Peishan; Ng, Wei Lun; Wu, Wei; Dai, Seping; Ning, Zulin; Wang, Shuqiong; Liu, Ying; Fan, Qiang; Zhou, Renchao (Frontiers in Plant Science, 2017)
Inferring the origins of hybrid taxa based on morphology alone is difficult because morphologically similar hybrids can arise from hybridization between different populations of the same parental species or be produced by hybridization of different parental species. In this study, we investigated the origins of two semi-creeping taxa in Melastoma, which are morphologically similar to a natural hybrid, M. intermedium, by sequencing a chloroplast intergenic spacer, nuclear ribosomal internal transcribed spacer (nrITS) and two low-copy nuclear genes (tpi and cam) in these taxa and their putative parental species. Our sequence analysis results provide compelling evidence for the hybrid status of the two semi-creeping taxa: one originating from hybridization between M. dodecandrum and M. malabathricum, and the other between M. dodecandrum and M. normale. The origins of these hybrids are therefore clearly different from M. intermedium, and morphological similarity for the three hybrids is most likely due to their origins from hybridization between the same creeping species M. dodecandrum and a different erect species in each of the three cases. We also observed low rate of introgression from M. normale to M. dodecandrum, and genetic exchange between them may transfer adaptive traits to M. dodecandrum. Rare occurrence of these two hybrids may be due to small range overlaps between parental species in one case, and different flowering periods between parental species in the other.